MOLECULAR CHARACTERIZATION OF INFLUENZA B VIRUS OUTBREAK ON A CRUISE SHIP IN BRAZIL 2012 - Borborema, Samanta Etel Treiger; Silva, Daniela Bernardes Borges da; Silva, Kátia Corrêa Oliveira; Pinho, Margarete Aparecida Benega; Curti, Suely Pires; Paiva, Terezinha Maria de; Santos, Cecília Luiza Simões (Revista do Instituto de Medicina Tropical de São Paulo, 2014)
In February 2012, an outbreak of respiratory illness occurred on the cruise ship MSC Armonia in Brazil. A 31-year-old female crew member was hospitalized with respiratory failure and subsequently died. To study the etiology of the respiratory illness, tissue taken at necropsy from the deceased woman and respiratory specimens from thirteen passengers and crew members with respiratory symptoms were analyzed. Influenza real-time RT-PCR assays were performed, and the full-length hemagglutinin (HA) gene of influenza-positive samples was sequenced. Influenza B virus was detected in samples from seven of the individuals, suggesting that it was the cause of this respiratory illness outbreak. The sequence analysis of the HA gene indicated that the virus was closely related to the B/Brisbane/60/2008-like virus, Victoria lineage, a virus contained in the 2011-12 influenza vaccine for the Southern Hemisphere. Since the recommended composition of the influenza vaccine for use during the 2013 season changed, an intensive surveillance of viruses circulating worldwide is crucial. Molecular analysis is an important tool to characterize the pathogen responsible for an outbreak such as this. In addition, laboratory disease surveillance contributes to the control measures for vaccine-preventable influenza.